THE LEVEL OF PATIENTS TRUST TO THE HEALTH CARE SYSTEM AND ITS INFLUENCE ON SATISFACTION BY MEDICAL CARE - Яворський, А. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
This article is devoted to studying the level of patients trust to the health care system and its impact on satisfaction by medical care. The study involved 530 patients completing treatment in the surgical departments of Ivano-Frankivsk region inpatient facilities. It is set that almost 60% polled patients not enough trust doctors and third of respondents does not know the own physicians. It substantially increases the chances of dissatisfaction by medical care (OR= 4,11; 95% СІ: 1,67–10,14, р<0,001 and OR=1,96; 95% СІ: 1,33–2,90 accordingly; р<0,001), and also promotes the inefficient use of health care system resources as a result of groundless hospitalization (in 18,8% cases).